Rhetoric for Tourism Business: Worksheets - Potočnik Topler, Jasna (2021)
Rhetoric is the skill of persuasion. It has accompanied people for millennia, and the foundations of rhetorical theory were laid by the Ancient Greek thinker Aristotle. Through historical periods it has undergone development, rises and also falls. Today we are increasingly aware of the importance of familiarity with this skill in very broad fields of public and private life, for ultimately it contributes to better reading literacy of individuals and society. One of the aims of teaching rhetoric at the Faculty of Tourism of the University of Maribor is to prepare students to analyse and more accurately and precisely formulate arguments and persuasive techniques in everyday life, ranging from personal conversations to the media, study situations and the composition of expert texts. Equally it aims to familiarise students with various discourses, to teach them independent, more self-confident, clear, structured and critical expression of views and to formulate structured short and long texts. The booklet contains work sheets that will serve as support points in aiding rhetoric in business communication, when the focus is on topics such as history, rhetorical genres, canons, persuasion and language. We will also focus attention on the legal aspects of communication.The publication is a translated and supplemented edition of worksheets published in 2018. (LINK)
Keywords: rhetoric; tourism; writing for tourism; interpretation in tourism; public speaking